68.8k views
1 vote
Solve.

x2 + x – 6 = 0



{2, –3}


{6, –1}


{3, –2}

{2, 3}

1 Answer

1 vote

Answer:

x = - 3, x = 2

Explanation:

Given

x² + x - 6 = 0 ← in standard form

To factorise the quadratic

Consider the factors of the constant term (- 6) which sum to give the coefficient of the x- term (+ 1)

The factors are + 3 and - 2, since

3 × - 2 = - 6 and 3 - 2 = + 1, hence

(x + 3)(x - 2) = 0 ← in factored form

Equate each factor to zero and solve for x

x + 3 = 0 ⇒ x = - 3

x - 2 = 0 ⇒ x = 2

User Rahmat Ali
by
6.8k points